2022
DOI: 10.3390/en15155473
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Energy and Food Security in Africa with Instrumental Variables Analysis

Abstract: The well-being of human populations and their sustainable development are strongly predicated on energy and food security. This is even more true of Africa due to often suboptimal food production, undernourishment, and extreme poverty. This article researches the relationship between energy and food security using Cobb–Douglas production functions based on the World Development Indicators data for 28 African countries. The methodological approach includes cross-sectional dependence and unit root tests, instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…Given these statistics, it appears that most of the work done so far on the link between energy and food security has focused on the microlevel (Ahlborg and Sjöstedt 2015 ; Islam et al 2017 ; Kirubi et al 2009 ; Mushtaq et al 2009 ). The present study goes beyond the previous studies by adopting a macroeconomic perspective in line with previous authors such as Sola et al ( 2016 ), Nkiaka et al ( 2021 ), Candelise et al ( 2021 ), and Zakari et al ( 2022 ). In addition, several theories have been developed to show the link between energy and food security.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Given these statistics, it appears that most of the work done so far on the link between energy and food security has focused on the microlevel (Ahlborg and Sjöstedt 2015 ; Islam et al 2017 ; Kirubi et al 2009 ; Mushtaq et al 2009 ). The present study goes beyond the previous studies by adopting a macroeconomic perspective in line with previous authors such as Sola et al ( 2016 ), Nkiaka et al ( 2021 ), Candelise et al ( 2021 ), and Zakari et al ( 2022 ). In addition, several theories have been developed to show the link between energy and food security.…”
Section: Introductionsupporting
confidence: 68%
“…Nkiaka et al ( 2021 ) through spatial analysis found that energy security improves food security. Using Cobb–Douglas production functions based on the World Development Indicator data for 28 African countries, Zakari et al ( 2022 ) find that promoting energy security promotes food security. This is possible because food production and distribution are energy-intensive activities.…”
Section: Literature Review: Energy Poverty and Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…The report specifically showed that this group is more likely to be unsatisfied in life, food insecure, and have limited opportunities for skill development. However, other studies have also observed these factors (life satisfaction and food insecurity) to influence energy poverty (Bielski et al, 2021;Churchill et al, 2021;Lin and Okyere, 2022a;Zakari et al, 2022). Therefore, we expect them to indirectly explain how the intersection between females and disabilities affects energy poverty.…”
Section: Literature Reviewmentioning
confidence: 87%
“…It is not surprising that recent studies have observed energy poverty and food insecurity to interact. Using data on Africa, Zakari et al (2022) found food insecurity positively associated with energy poverty. In Poland, food insecurity has been noted to be an obstacle to achieving energy security (Bielski et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%